The formation of an ecological culture among the students of school (Kashkadarya region) on the example of (Eurasian Journal of History, Geography and Economics, 2026)
This article, using the example of Kashkadarya region, is devoted to forming ecological culture in school-age children. It teaches children to view nature as a part of themselves and of people, to have proper attitudes toward the natural resources they use and the surrounding environment, and to love, respect, and protect nature.